The effect of organizational justice and employee satisfaction: A bibliometric analysis of the literature (Asian Journal of Economics and Business Management, 2022)
Organizational justice has a benchmark for a person's feelings from the results of an employee's assessment of an organization, this is related to making organizational decisions to become an important element for the workers by involving decision-making regarding policies and regulations in the organization. This may give an immediate impression of the needs of labor organizations in terms of the roles of workers. The purpose of this research is to provide an assessment of the relationship between organizational justice and employee satisfaction as a related one. The level of employee satisfaction is positively or negatively affected because the perception of organizational justice is felt directly by employees who are treated fairly in the workplace. Job satisfaction is positively motivated by work as such. The concept of organizational justice and satisfaction becomes an important factor when the interests of human resources are taken into account in the business environment. The purpose of this study was to measure the effect of organizational justice on individual employee satisfaction within the organization. The concepts of organizational justice and job satisfaction have important preparations for an organization to achieve them. Articles were taken from the Publish or Perish database, with a total of 200 articles found in the period 2018-2023 that were analyzed. Then the researcher grouped and visualized using the VOS viewer application to be able to identify the data that had been collected. This literature study provides an appropriate meeting point regarding the themes of organizational justice and employee satisfaction at the academic level.